Structure-Function Analysis of the Shigella Virulence Factor IpaB - Guichon, Andrea (American Society for Microbiology, 2001)
Infection by the gram-negative bacterium Shigella flexneri results in dysentery, an acute inflammatory disease of the colon. Essential events in the pathogenesis of Shigella infections include bacterial invasion of epithelial cells, escape from the phagosome, and induction of apoptosis in macrophages. The Shigella virulence factor invasion plasmid antigen B (IpaB) is required for all of these processes. Induction of apoptosis is dependent on IpaB binding to the cysteine protease caspase-1 (Casp-1). The activation of this enzyme triggers both apoptosis and release of the proinflammatory cytokine interleukin-1β. Several IpaB mutants were generated to correlate function with protein subdomains. We determined that the N-terminal portion of IpaB is necessary for stable expression of IpaB. A putative amphipathic α-helical domain preserves the structure of IpaB. We found 10 consecutive residues within the amino terminus of the hydrophobic region that play a critical role in invasion, phagosomal escape, and cytotoxicity. An IpaB mutant carrying a mutation in this region binds to Casp-1 yet is not cytotoxic, even following direct delivery to the macrophage cytoplasm. These results indicate that the association between IpaB and Casp-1 is only a step in the activation of macrophage apoptosis.